Carlos Alberto SCOLARI. (2020). Cultura snack. Lo bueno, si breve... - Nigro Moser, Patricia María (2022)
The penultimate book by the Argentine scholar affiliated with the Pompeu Fabra University is Cultura snack. Lo bueno, si breve... Once again, the text demonstrates the author’s expertise in communication and digital culture, for which he is widely recognized through the blog Hipermediaciones.com and through numerous books and articles. Among these, two particularly noteworthy works are Narrativas Transmedia. Cuando todos los medios cuentan (2013) and Las leyes de la interfaz (2021, expanded 2nd edition).